Phenotypic diversity of breast cancer-related mutations in metalloproteinase-disintegrin ADAM12 - Qi, Yue; Duhachek-Muggy, Sara; Li, Hui; Zolkiewska, Anna (My University, 2014)
Six different somatic missense mutations in the human ADAM12 gene have been identified so far in breast cancer. Five of these mutations involve highly conserved residues in the extracellular domain of the transmembrane ADAM12-L protein. Two of these extracellular mutations, D301H and G479E, have been previously characterized in the context of mouse ADAM12. Three other mutations, T596A, R612Q, and G668A, have been reported more recently, and their effects on ADAM12-L protein structure/function are not known. Here, we show that ADAM12-L bearing the G668A mutation is largely retained in the endoplasmic reticulum in its nascent, full-length form, with an intact N-terminal pro-domain. The T596A and R612Q mutants are efficiently trafficked to the cell surface and proteolytically processed to remove their pro-domains. However, the T596A mutant shows decreased catalytic activity at the cell surface, while the R612Q mutant is fully active and comparable to the wild-type ADAM12-L. The D301H and G479E mutants, consistent with the corresponding D299H and G477E mutants of mouse ADAM12 described earlier, are not proteolytically processed and do not exhibit catalytic activity at the cell surface. Among all six breast cancer-associated mutations in ADAM12-L, mutations that preserve the activity - R612Q and L792F - occur in triple-negative breast cancers, while loss-of-function mutations - D301H, G479E, T596A, and G668A - are found in non-triple negative cancers. This apparent association between the catalytic activity of the mutants and the type of breast cancer supports a previously postulated role of an active ADAM12-L in the triple negative breast cancer disease.
Citation: Qi Y, Duhachek-Muggy S, Li H, Zolkiewska A (2014) Phenotypic Diversity of Breast Cancer-Related Mutations in Metalloproteinase-Disintegrin ADAM12. PLOS ONE 9(3): e92536. https://doi.org/10.1371/journal.pone.0092536
Keywords: ADAM12; Breast cancer; Mutations; Disintegrin; Metalloproteinase